2020
DOI: 10.22146/ijc.50330
|View full text |Cite
|
Sign up to set email alerts
|

<i>Myristica fragrans</i> Shells as Potential Low Cost Bio-Adsorbent for the Efficient Removal of Rose Bengal from Aqueous Solution: Characteristic and Kinetic Study

Abstract: In the present study, the Myristica fragrans shells (MFS) was used as low-cost bio adsorbent for the removal of Rose Bengal (RB) dye from aqueous solutions. The characteristics of MFS powder were studied before and after adsorption using different techniques such as Fourier transform Infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), BET and BJH surface area analysis, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Batch adsorption was adopted to evaluate the effect of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Comparable behaviour has been announced in previous works and it has been suggested that increasing the dose of adsorbents, beside to decreasing the efficient surface area, may be due to increasing the diffusion path length, causes a decrease in the adsorption efficiency (Waheeb et al 2020;Gurunathan et al 2019).…”
Section: Effect Of Adsorbent Amountsupporting
confidence: 67%
“…Comparable behaviour has been announced in previous works and it has been suggested that increasing the dose of adsorbents, beside to decreasing the efficient surface area, may be due to increasing the diffusion path length, causes a decrease in the adsorption efficiency (Waheeb et al 2020;Gurunathan et al 2019).…”
Section: Effect Of Adsorbent Amountsupporting
confidence: 67%
“…The hydroxyl group (O-H) of acrylic acid and alginatestretching vibration caused all the hydrogels to exhibit a recognizable wide-stretching frequency at 3000-3500 cm −1 . A weak band with several peaks at 1040, 1113, 1236, and 1262 cm −1 is ascribed to alcohols, carboxylic acids, and ethers (1000-1320 cm −1 is attributed to C-O stretch), while a prominent peak at 1713-1725 cm −1 is indexed to the carbonyl group (C=O) stretching vibration for all components [14][15][16]. After the adsorption of TC and PH, we find the expansion of the bands due to the presence of an abundance of drug hydroxyls, the occurrence of electrostatic attraction, and the effect of van der Waals forces [17].…”
Section: Characterizationmentioning
confidence: 99%
“…Through TGA, it was found that the composite bentonite/TiO 2 is more stable than bentonite clay because of the specificity of the nanomaterial, which led to an increase in the stability of the overlay. 20,21 Effect Weight and pH on Adsorption In Figure 5 a, it is shown that the effective weight of the adsorption process is 0.1 g. The removal rate of the drug substance increases with the weight of the adsorbent, and on the other hand, the decrease in the amount of adsorption with the increase in the weight of the adsorbent surface can be attributed to the non-saturation of the adsorption sites of the surface during the adsorption process, in addition to the interactions that occur between the particles (such as the occurrence of agglomeration), which occurs When using high weights on the adsorbent surface. Such interference can lead to a decrease in the surface area of the adsorbent.…”
Section: Thermo Gravimetric Analysis (Tga)mentioning
confidence: 99%